POLITICAL INFLUENCE AND THE PROLIFERATION OF TERTIARY INSTITUTIONS: IMPLICATIONS FOR QUALITY AND SUSTAINABLE TERTIARY EDUCATION DEVELOPMENT - Ogunode, Niyi Jacob; Isa, Asmau Jumai (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This paper examines the implications of establishing tertiary institutions based on political considerations, constituency demands, and personal prestige. Method: The study argues that such motivations often lead to the proliferation of poorly planned institutions characterized by inadequate funding, insufficient infrastructure, and declining academic standards. Results: The paper further highlights how politically motivated establishment of institutions contributes to duplication of academic programmes, inefficient allocation of resources, and weak institutional governance. It concludes that tertiary institutions should be established based on strategic educational planning, manpower needs, and sustainable funding mechanisms. Novelty: The study recommends stronger regulatory frameworks, evidence-based educational planning, and adherence to national higher education policies to ensure the sustainable development of tertiary education systems.